Fast And Simple NEMO Authentication Via Random Number. - Tan, Tat Kin; Samsudin, Azman (2007)
Network Mobility (NEMO), derived from Mobile Internet Protocol version 6 (MIFV6) technology, has been evolving and expanding in very rapidity manner across very short period of time. In MIPv6 technology, the Access Router (AR) plays important roles such as provide sessions connectivity and safe-guarding communications protocol.